ESC GUIDELINES FOR THE DIAGNOSIS AND TREATMENT OF ACUTE AND CHRONIC HEART FAILURE 2008 - Kenneth Dickstein; Alain Cohen-Solal; Gerasimos Filippatos; John J.V. McMurray; Piotr Ponikowski; Philip Alexander Poole-Wilson; Anna Stromberg; Dirk J. van Veldhuisen; Dan Atar; Arno W. Hoes; Andre Keren; Alexandre Mebazaa; et al. (Столичная издательская компания, 2016)
ESC Guidelines for the diagnosis and treatment of acute and chronic heart failure 2008.